2019
DOI: 10.1007/s11442-019-1624-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the vertical distribution pattern of land-use conversion in the loess hilly region of northern Shaanxi Province 1995–2015

Abstract: The mountainous and hilly region plays an important role in ecological safety and production in China. However, recent studies have poorly characterized the parallel structure of land use in the valleys of the mountainous and hilly region using topographic factors (e.g. elevation, slope, aspect). Here, the loess hilly region of northern Shaanxi Province is used as a representative case area to analyze the vertical distribution pattern of land-use conversion using the relative elevation concept and the HAND ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Vegetation restoration, leading to clear land use changes, is an effective measure to reduce soil erosion and promote carbon sequestration on the Loess Plateau (Fu et al, 2017;Cao et al, 2019). However, many observations have indicated that revegetation decreases the soil water content and exacerbates the soil desiccation problem due to an increase in ET in the planted forest restricting plant growth (Wang et al, 2011;Jia et al, 2017).…”
Section: Implications For Ecosystem Restoration Managementmentioning
confidence: 99%
“…Vegetation restoration, leading to clear land use changes, is an effective measure to reduce soil erosion and promote carbon sequestration on the Loess Plateau (Fu et al, 2017;Cao et al, 2019). However, many observations have indicated that revegetation decreases the soil water content and exacerbates the soil desiccation problem due to an increase in ET in the planted forest restricting plant growth (Wang et al, 2011;Jia et al, 2017).…”
Section: Implications For Ecosystem Restoration Managementmentioning
confidence: 99%
“…Thus, measures such as building silt arrester, gully land consolidation were carried out to control soil erosion while also construct high quality cropland to supplement cropland (Liu and Li, 2017b;Li et al, 2021b). After years of comprehensive management, it witnessed significant changes of the spatial form of production-ecology, forming a spatial pattern of vegetation restoration on the hill and agricultural production in the gully (Cao et al, 2019). The formation of gully agriculture has laid a good foundation for the sustainable development of regional agriculture (Qu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%